Effects of Lecithin Supplementation in Feed of Different fat Levels on Serum Indexes and Liver Health of Laying Hens - Hu, Gui-Li; Xiong, Juan; Liu, Yang; Yang, Hong-Jun; Hu, Ling-Ling; Chen, Peng; Wang, Xin; Liao, Shuang; Lv, Tuo; Liu, Chun-Jie; Huang, Peng; Lin, Qian (Frontiers in Physiology, 2022)
The aim of this experiment was to investigate the effect of soy lecithin on serum-related indicators and liver health in laying hens under the influence of high-fat diets. 180 peak laying hens at 40 weeks of age were randomly assigned to one of the four diets using a 2 × 2 factorial and fed for 5 weeks. The results showed that compared to the low-fat group, the high-fat group had lower egg production (p < 0.05) and higher average daily feed intake and feed-to-egg ratio (p < 0.05). At the 21st day, the serum levels of triglyceride (TC) and superoxide dismutase (SOD) were higher (p < 0.05), high-density lipoproteins cholesterol (HDL-C) levels were lower (p < 0.01), catalase (CAT) activity was lower (p < 0.05), TC and malondialdehyde (MDA) levels in liver were higher (p < 0.01) and SOD activity in liver was lower (p < 0.05) in layers supplemented with soy lecithin. CAT activity in serum was increased (p < 0.01) and total antioxidant capacity (T-AOC) activity in the liver was decreased (p < 0.05) after increasing the dietary fat concentration. The addition of soy lecithin and the increase in dietary fat concentration had a highly significant interaction on serum CAT activity and liver TC content in layers (p < 0.01). At the 35th day, the serum alanine aminotransferase (ALT) activity was higher (p < 0.01), serum glutathione peroxidase (GSH-Px) and CAT activity were higher (p < 0.05), and serum triglyceride (TG) content and total T-AOC capacity activity were lower (p < 0.05) in layers supplemented with soy lecithin. Increasing dietary fat concentration decreased alanine aminotransferase (ALT), aspartate aminotransferase (AST) and GSH-Px activity in serum (p < 0.05). However, it increased TG and MDA content in liver (p < 0.05), and highly decreased SOD content in liver (p < 0.01) in layers. The addition of soy lecithin and increasing dietary fat concentration had a highly significant reciprocal effect on serum ALT viability and CAT viability (p < 0.01) and liver TG and MDA content and SOD viability (p < 0.05) in layers. In conclusion, feeding high-fat diets will adversely affect the laying performance of laying hens, while long-term addition of lecithin can improve the blood lipids and liver lipids of laying hens, enhance the antioxidant capacity of the liver, and maintain liver health.